Anti-inflammatory and antioxidant traditional Chinese Medicine in treatment and prevention of osteoporosis - Li, Qian; Tian, Ciqiu; Liu, Xiangjie; Li, Dinglin; Liu, Hao (Frontiers in Pharmacology, 2023)
Osteoporosis is a metabolic bone disease characterized by reduced bone mass and impaired microarchitecture. This disease can make bones weaker and increase the risk of fractures. Osteoporosis is caused by two main factors, an increase in the activity or number of osteoclasts and a decrease in the number or viability of osteoblasts. Mechanisms such as estrogen deficiency, aging, chemical agents, and reduced mechanical loading have been well reported to be associated with osteoporosis. Recently, an increasing number of studies have shown that inflammation and oxidative stress are also associated with osteoporosis. The main drugs currently available for the treatment of osteoporosis include bisphosphonates and selective estrogen receptor modulators (SERMs). These drugs are effective for estrogen deficiency and aging-induced osteoporosis, but lack specificity for inflammation and oxidative stress-induced osteoporosis. In addition, these drugs have some limitations that are attributed to various side effects that have not been overcome. Traditional Chinese medicine (TCM) have been applied in osteoporosis for many years and has a high safety profile. Therefore, In this review, literature related to herbal medicines that have an effect on inflammation and oxidative stress-induced osteoporosis was searched. Moreover, the pharmacologically active ingredients of these herbs and the pathways were discussed that may contribute to the discover of more safe and effective drugs for the treatment of osteoporosis are discussed.